KAJIAN LAHAN PARKIR DI PUSAT PERBELANJAAN MALL SAMARINDA CENTRAL PLAZA (SCP) SAMARINDA - BAGIO, ARI (KURVA S JURNAL MAHASISWA, 2017)
Parking is one of the most important elements in the urban transport as it well affect the modal choice as well as the effect on the community and the transportation system in the city itself either short or long term basis the trade center area. Samarinda city is one area of dense activity. As well as the population growth is very rapid.As ready of this growth, the number of new buildings that have traction and the seizure of vehicles is quite high, such as the following: mall, central offices, housing and others. Which makes the limited space for the movement of vehicles in the city of Samarinda activity of engine vehicles in the city of Samarinda also quite high each day so we need an area that is strategic to accommodate motorists and car both private vehicles woild also vehicles pub;ic transport them.Observations were made for 5 days with longer observation time 12 hours (10.00-22.00) . Data analysis included accumulated parking, parking duration, turn over parking, parking indeks, parking volume, parking capacity, parking levies.Average accumulated during the study for two wheels at 190.4/ day and for four wheels 98.8/day. Most parking duration is less than 1.5 hours, and turn over average parking during the study for two wheels at 0.152 and for four wheels of 0.196. and income parking fees highest for two wheels is Rp. 2.672.000, and for four wheels is Rp. 3.301.400, and for parking indeks for two wheels is 5.46% and for four wheels is 10.64%.